x2 + 4 = 0
then get the x on one side.
x2 = -4
then find the square root of both which would cancel the square on the x.
therefore the answer is: x = the square root of -4 = i squared root 4, which is a complex number ( imaginary number) since you cannot find the square root of oa negative number
It can be solved by using the quadratic equation formula.
It cannot be solved because the discriminant of the quadratic equation is less than zero
Factor it. (x - 8)(x - 2) x = 2, 8
0 squared is 0. Zero times zero equals zero.
It has no solutions because the discriminant is less than zero.
It equals 0. Zero times zero equals zero.
It can't be solved because the discriminant of the given quadratic equation is less than zero meaning it has no real roots.
It can not be factored because its discriminant is less than zero
p is obviously zero because any number x plus 0 equals itself.
Without knowing what "x" is, we cannot say what the answer will be. And without knowing the answer, we cannot solve for "x". Set x at zero, for example. Zero squared is zero, plus 6 time zero which is zero, minus 55. Your answer is then -55. Set x at one, for example. One squared is one, plus 6 times 1 which is six, minus 55. Your answer is then -48. Etc.
x2-2x+1 = 0 (x-1)(x-1) = 0 x = 1 and also x = 1
x = 5 / 6squared + 7
you shouldn't be cheating u tard. it -24x +3 is ur answer
3x^2 + 5x - 8 = 0 + 8 + 8 3x^2 + 5x = 0 8x ^2 = 0
X = 0 (zero) Y = -1 (neg 1)
Equals anything... x is a variable. If that equation was set equal to zero then you could solve for x, but that is not what you have asked.
That factors to (x + 1)(x - 3) x = -1, 3
It is, as stated, 2x2 + x - 1 = 0. That is the quadratic form.
It Equals 2
It can't be solved because the discriminant of this quadratic equation is less than zero
So u have the function x2-4=0 Now because 4 is a squared number, its square root is 2 (x+2)(x-2)=0
If x2 is zero, then x=0 (and no, that is not an emoticon) The only root of zero is zero.
x2 + X -6 =0 so X2 + X = 6 so X2 = 6-x so X = square root of (6-x) That's as far as I can get it.
It is, as stated, x2 - 5x + 25/4 = 0